Fisiologia da maternidade tardia: síntese de estudos e evidências científicas - Silva, Gabriel Vinicius Magella e (2025)
The postponement of motherhood has become a growing trend in several countries, influenced by social, economic, and professional factors, as well as by increased life expectancy. This qualitative and descriptive study aims to reflect on the physiological and bioethical aspects involved in late pregnancy, particularly among women aged 35 and over. Through a narrative literature review, scientific evidence was analyzed pointing to both the clinical risks associated with advanced maternal age and the advances that enable greater safety in the gestational process. The importance of conscious reproductive planning and adequate prenatal care is also discussed as tools to minimize associated risks. Although late motherhood presents physiological challenges, it can be feasible and safe when supported by knowledge, medical care, and respect for women’s reproductive decisions from an ethical perspective.